Lumine. Vol. 3 - Krogell, Emma (WEBTOON Unscrolled, 2025)
"In a world where weredogs, witches, and humans live side by side, Lumine was a down-on-his-luck weredog with nowhere to turn ... until he met Kody. Kody and Lumine barely survived being kidnapped by witch hunters. Thankfully, the witch kid and his bodyguard are safe, for now. Kody's father, Aiden, still wants Lumine to protect his son, and even more so, be his friend. Lumine might be the one who can finally bring the lonely, troubled Kody out of his shell. Things are also looking brighter because Calla, Kody's friend turned bully, has realized the error of her ways. As thanks for Kody and Lumine saving her life, she persuades all the witch kids at school to leave Kody alone. But trouble still looms. Lumine is actually a werewolf, a rare and powerful type of magical being thought to be extinct. It's dangerous to be a werewolf in this world, and someone is hunting him"--